Bible: the story of the King James Version 1611 - 2011 - Campbell, Gordon (Oxford University Press publications, 2011)
Illustrated with reproductions from early editions of the King James Bible, Bible: The Story of the King James Version offers an authoritative history of this renowned translation, ranging from the Bible's inception to the present day.--From publisher description